ANALISIS PENGANGKATAN TENAGA KERJA HONORER MENJADI CALON PEGAWAI PEMERINTAH DENGAN PERJANJIAN KERJA (PPPK) DI KABUPATEN BANTAENG - Kanti, Nova Sri; Madani, Muhlis; Abdi, Abdi (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2023)
The purpose of this study was to find out the implementation of the appointment of honorary workers to become prospective government employees with work agreements in Bantaeng Regency. This study  used qualitative methods. From the use of qualitative methods. Collecting data used interviews, observation, and documentation. This study was conducted at the Education and Culture Office of Bantaeng Regency. The informants of this research were 5 people . The results showed that the process of appointing honorary workers to be prospective government employees with a work agreement (PPPK) in Bantaeng Regency had been carried out well, according to the indicators described by the researcher, namely identifying vacant positions, seeking job information through job analysis, determining candidates. right, choosing the most appropriate recruitment methods, selecting candidates who were deemed to meet the job requirements, screening candidates, making job offers, starting work. Where the appointment process had been carried out in accordance with government regulations, although the results of the appointment had not been able to drastically reduce honorary staff.